Observation on the Ecology of Tectona grandus in the Central Provinces - Hewetson, C. E. (Indian Forester, 1941)
The main points of the Ecology of teak int the Central Provinces are discussed and four suggestions made: (i) The soil derived from Trap rock is especially suitable to teak and that this is due to these soils being more moisture-retentive than those derived from sandstone or crystalline rocks. (ii) Fire protection is normally helpful to teak in this area.(iii) The other species present in the forest play a large part in the establishment of teak seedlings, (iv) The combination of teak and bamboo may be a true climatic climanx, but the loose use of the word "teak forest" to describe a formation m which teak trees form a varying proportion of the crop and where it is one of a number of species is dangerous to clear thinking. For the present it is better to regard forest in which teak forms a higher pro- portion of the crop than usual as a seral type.